Strategi Pendidikan Multikultural dalam Pembelajaran Pendidikan Agama Islam (PAI) di SD Islam Terpadu Al-Abqari Kota Subulussalam Provinsi Aceh - Mustafa, Mustafa; Pasaribu, Harsono (FONDATIA, 2024)
The aim of Islamic Religious Education (PAI) is not just to fill students' minds with knowledge and subject matter, but to cleanse their souls which must be filled with good morals and values. This is in accordance with the aim of multicultural education, namely to create a harmonious life in a pluralistic society. The aim of this research is to determine multicultural education strategies in learning Islamic Religious Education (PAI) at the AL-ABQARI Integrated Islamic Elementary School, Subulussalam City, Aceh Province. This research method is a qualitative approach. The research subjects (informants) were school principals, Islamic Religious Education (PAI) teachers and students. Data collection techniques for this research are observation and interviews. The results of this research are that multicultural education strategies in Islamic Religious Education (PAI) learning are: 1) Teachers teach with teaching and learning activities by creating heterogeneous groups based on the division of groups of students of different genders, having different cultures; 2) Relationships between students in one group communicate with each other, work together and collaborate positively (human relations); 3) Single group studies, where the teacher explains in detail things that promote pluralism but does not emphasize social stratification in schools; 4) Teaching and learning activities use curriculum and learning materials that emphasize differences. Teachers empower the culture of students brought to school who come from different groups; 5) Teachers make a lot of effort to help students develop positive attitudes about group differences. The conclusion of this research is that Islamic Religious Education (PAI) learning at the AL-ABQARI Integrated Islamic Elementary School is carried out using a multicultural education strategy.